USING GROUP WORK AS A MEANS OF DEVELOPMENT COGNITIVE ACTIVITY OF STUDENTS IN CLASSES FROM GEOGRAPHICAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2022)
In article problems of use group robos in practice of the higher school on occupations from geographical disciplines as way of development of cognitive activity of students are considered. The analysis is sent to concept “group work”. It is shown results of use of group work to the higher school.
Keywords: group work; cognitive activity